Analysis of the Impact of Flyover Development on Communities in the Market - Jihan Melasari; Rafki Imani; Juni Saputra (Universitas Putra Indonesia YPTK Padang, 2020)
Traffic congestion that occurs almost everyday in Pekanbaru City has caused losses in travel time and economic losses such as waste of fuel, loss of productive time and health costs. One of the causes of this congestion is the growth of road infrastructure that is not proportional to the growth in the number of motorized vehicles. Besides that, the existence of Pasar Pagi Arengka at the Jl. HR Soebrantas and Jl. Soekarno-Hatta, Riau Province, has also added to the level of congestion. Overcoming this problem, the Riau government together with the Dinas Pekerjaan Umum (PU) of Riau Province built a flyover or overpass at Pasar Pagi Arengka junction to overcome the congestion problem. The research data was obtained by conducting a survey to the location through a questionnaire to the community around the flyover with the number of respondents determined as many as 60 respondents. Calculation analysis is performed using SPSS Statistics. The results of the study stated that the impact caused by the construction of a flyover at the intersection of Pasar Pagi Arengka in Pekanbaru, Riau Province, to the community was quiteinfluential.